The influence of chronoanalysis on the delivery of laboratory results in a sugar-alcoholic process - dos Santos Bernardo, Thaís; Luis Garcia Hermosilla, José; Cristine Scarduelli Pacheco, Bruna (Revista Gestão da Produção Operações e Sistemas, 2024)
Objective: The objective of this study is to describe the use of the chronoanalysis technique in laboratory processes of a medium-sized industry in the sugar and alcohol segment and its impacts on process improvement, in particular on the response time of analytical results. Theoretical Framework: Chronoanalysis is a technique that is based on the study of times and movements to identify and eliminate activities that do not add value to the process, aiming to optimize time and improve efficiency. Methodology/Approach: Research of an applied nature, with a descriptive objective, based on a case study of a sugar and alcohol plant, addressing qualitative aspects of the quality control sector where it presents the mapping of activities. Results: The application of chronoanalysis concepts allowed us to identify and eliminate aspects that did not add value to the process, resulting in a significant reduction in analysis time by 33.65%. This improved the conditions for delivering results and facilitated the identification of flaws in the product manufacturing process. Contributions, practical and social implications: The study demonstrated that the application of chronoanalysis can have a positive impact on the efficiency of laboratory processes, reducing the turnaround time for results and contributing to improving quality and efficiency in the sugar and alcohol industry. Originality/Value: Your findings could be highly relevant to other industries wanting to improve their laboratory processes and reduce the risk of non-conformities. Keywords: Chronoanalysis. Study of time and movements. Standard time. Process mapping. Analyzes.